Gradient pore structure geopolymer asphalt mixture warm mixing agent and preparation method thereof
By using a geopolymer asphalt mixture warm mix agent with a gradient pore structure, the existing warm mix agent problems of disconnected pores, low water content and uneven water release are solved, achieving efficient water loading and uniform release, significantly improving performance of asphalt mixtures.
Patent Information
- Application Number
- CN202411457854.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
The existing natural zeolite warm mixing agents have problems such as non-connected pores, low water content, uneven water release rate and short water release cycle, which leads to poor warm mixing effect and high production cost of synthetic zeolite warm mixing agents.
A geopolymer asphalt mixture warm mix agent with a gradient pore structure is composed of recycled micro-powder, rice husk ash, sodium silicate solution, sodium hydroxide and deionized water. It is prepared through calcination, ball milling, freeze-drying and other processes to form a non-toxic mixture. The gradient pore structure of closed pores or semi-closed pores improves the adsorption capacity of water and the water release cycle of the pore structure.
A significant increase in the loading and water release cycle of the temperature mixing agent ensures that the rate of water release process is uniform, reducing the mixing temperature of asphalt mixture, and improving the performance of high and low temperature, water resistance damage and fatigue performance.
Smart Images

Figure CN119330623A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a geopolymer asphalt mixture warm mix agent with a gradient pore structure and also relates to a preparation method of the geopolymer asphalt mixture warm mix agent. Background Art
[0002] Asphalt pavement has been widely used in road engineering due to its good road performance, convenient construction and maintenance methods and many other advantages. In terms of highway construction and maintenance, traditional hot mix asphalt technology has made important contributions to the development of modern highway transportation. However, the high construction temperature of hot mix asphalt technology consumes a lot of energy and produces a lot of dust and exhaust gas, which does not meet the development requirements of energy conservation and environmental protection.
[0003] Warm mix asphalt mixture is a mixture that reduces the mixing temperature of asphalt mixture by 30-40℃ or more without changing the mix ratio and construction process of hot mix asphalt mixture. Its performance is equivalent to that of hot mix asphalt mixture. The most significant advantages of warm mix asphalt mixture over hot mix asphalt mixture are energy saving and emission reduction, convenient construction, and improved construction environment. At present, the production of warm mix asphalt mixture is mainly achieved by adding warm mix agent to asphalt mixture.
[0004] The natural zeolite warm mix agent currently used has gel and impurities in its pores, resulting in some pores being disconnected and low in water content, resulting in poor warm mix effect; while synthetic zeolite warm mix agent requires hydrothermal synthesis, which increases production costs. In addition, zeolite warm mix agent also has problems such as uneven water release rate and short water release cycle; and the incomplete release of water (residual water) in the warm mix agent will lead to a decrease in the low temperature performance and water stability of the asphalt mixture. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a geopolymer asphalt mixture warm mix agent, which has a gradient pore structure and no closed pores or semi-closed pores, thereby effectively increasing the amount of water adsorbed by the pore structure and increasing the water carrying capacity of the warm mix agent. Moreover, since the pore structure is arranged in a gradient (gradually released from large pores to small pores), the water release period of the warm mix agent is effectively increased while ensuring that the water release rate of the water release process is uniform. Another purpose of the present invention is to provide a method for preparing the above-mentioned geopolymer asphalt mixture warm mix agent.
[0006] Technical solution: The geopolymer asphalt mixture warm mix agent of the present invention is composed of the following components in parts by weight: 65-85 parts of regenerated micropowder, 15-35 parts of rice husk ash, 15-20 parts of sodium silicate solution, 5-10 parts of sodium hydroxide and 10-20 parts of deionized water.
[0007] The regenerated micro powder is the powder produced in the process of preparing the regenerated aggregate, and then the powder is treated as follows: the regenerated micro powder is first calcined at 750-950°C for 2-2.5 hours, and then naturally cooled and ball milled in a planetary ball mill for 5-15 minutes. The average particle size of the regenerated micro powder prepared is 40-50 μm, and the specific surface area is 200-450 m 2 / kg; the regenerated micropowder is pretreated to stimulate its activity so that it can be hydrated again, and at the same time it helps it to form a gradient pore structure when it is molded into a geopolymer, which is beneficial to the storage and release of water, thereby improving the warm mix effect of the asphalt mixture; and it can also ensure that it will not affect the mixing and overall porosity of the asphalt mixture.
[0008] The rice husk ash is prepared by the following method: firstly treated with hydrochloric acid, then neutralized and washed, and finally calcined at high temperature. The hydrochloric acid soaking treatment is to remove excess metal ions, and the neutralization and washing treatment is to adjust the pH value to ensure subsequent reaction with the alkaline substances in the formula. The addition of rice husk ash to the formula is to utilize the amorphous silicon dioxide in the rice husk ash and the silicon-aluminum ratio of the regenerated micropowder to prepare the geopolymer; on the other hand, the internal structure and external structure of the rice husk ash prepared by the present invention have a micron-scale honeycomb hole interlayer, which can cooperate with the regenerated micropowder to adjust the pore structure inside the geopolymer.
[0009] The calcination temperature is 850-900°C, and the calcination time is 1-1.5h.
[0010] The Baume degree of the sodium silicate solution is 35.0 to 37.0. Baume degree is an indicator for measuring the concentration of the solution, which has a great influence on the flow properties of the geopolymer slurry during molding, because the slurry must be injected into the mold of the directional freezing equipment, so the slurry cannot be too viscous and must have good fluidity.
[0011] The sodium hydroxide is in the form of solid flakes (the dissolution speed of the flakes in the alkaline activator is relatively slow, the dissolution process is relatively stable, and the heat during dissolution is relatively small), and the purity is 99%.
[0012] The resistivity of the deionized water is 10-18 MΩ·cm, and the purity is greater than 98.5%.
[0013] The preparation method of the geopolymer asphalt mixture warm mix agent comprises the following steps:
[0014] (1) Mixing the formulated amount of recycled micro powder and rice husk ash to obtain powder A, wherein the silicon-aluminum ratio in the powder A is 2 to 1:1;
[0015] (2) mixing the sodium silicate solution, flaky sodium hydroxide and deionized water in the formula amount, stirring until the sodium hydroxide is completely dissolved, and then standing for aging to obtain solution B;
[0016] (3) adding powder A into a slurry mixer, slowly adding solution B during the stirring process, and stirring thoroughly for 3 to 5 minutes to obtain a geopolymer slurry;
[0017] (4) placing the geopolymer slurry into a mold of a directional freezing device for rapid freezing treatment;
[0018] (5) The gradient pore structure geopolymer obtained after the rapid freezing treatment is dried using a freeze dryer, and then cured. After curing, the geopolymer is ground into powder to obtain a geopolymer asphalt mixture warm mix agent.
[0019] In step (2), the aging time is 12 hours. The purpose of aging is to make the alkaline activator component more uniform and more stable.
[0020] Wherein, in step (4), the freezing temperature is -30 to -20°C, the freezing direction is from bottom to top, the freezing rate is 0.5 to 2°C / min, and the freezing time is 30 to 60 min.
[0021] Wherein, in step (5), the freeze drying temperature is -15°C, the vacuum degree is 20Pa, and the drying time is 24h. After freeze drying, a gradient pore structure is formed.
[0022] Wherein, in step (5), steam curing is used for curing, and the curing period is 7 days.
[0023] In step (5), the particle size of the polymer with gradient pore structure after grinding is 25-45 μm, and the specific surface area is 150-250 m 2 / kg.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0025] (1) The geopolymer asphalt mixture warm mix agent of the present invention has a gradient pore structure and no closed pores or semi-closed pores, so that it can greatly increase its water absorption during the curing process, thereby increasing the water carrying capacity of the warm mix agent. In addition, since the pore structure is arranged in a gradient (gradually released from large pores to small pores), it can effectively increase the water release cycle of the warm mix agent and make the water release rate uniform.
[0026] (2) The geopolymer asphalt mixture warm mix agent of the present invention is prepared by using recycled micro powder and rice husk ash, which makes full use of solid waste materials while saving energy and reducing emissions, and has a simple preparation process, which is conducive to large-scale promotion and application;
[0027] (3) Compared with hot-mix asphalt mixture, the gradient pore structured polymer asphalt warm mix agent of the present invention can significantly reduce the mixing temperature of the asphalt mixture, while also improving the high and low temperature performance, water damage resistance and fatigue performance of the asphalt mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the gradient pore structure geopolymer asphalt mixture warm mix agent obtained in Example 1;
[0029] Figure 2 Thermogravimetric analysis results of the gradient pore structure geopolymer asphalt mixture warm mix agent and Aspha-min (synthetic zeolite) warm mix agent of Example 1;
[0030] Figure 3 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0031] The regenerated micropowder used in the embodiments of the present invention was provided by Yangzhou Huimin Renewable Resources Co., Ltd., the rice husk was provided by Shanghai Wolu Trading Co., Ltd., the sodium silicate solution was provided by Jiashan Yourui Refractory Materials Co., Ltd., and the sodium hydroxide flakes were provided by Sinopharm Chemical Reagent Co., Ltd.
[0032] Example 1
[0033] The preparation method of the gradient pore structure geopolymer asphalt mixture warm mix agent of the present invention comprises the following steps:
[0034] (1) preparing 80 parts by weight of regenerated micropowder, 20 parts by weight of rice husk ash, 20 parts by weight of sodium silicate solution, 5 parts by weight of sodium hydroxide and 10 parts by weight of deionized water;
[0035] (1.1) Pretreatment of the regenerated micropowder: first heat activation treatment at 750°C for 2 h, then ball milling for 10 min after cooling; the average particle size of the prepared regenerated micropowder is 45 μm, and the specific surface area is 400 m 2 / kg;
[0036] (1.2) Preparation of rice husk ash: First, the rice husk is soaked in hydrochloric acid to remove metal ion impurities such as iron ions to improve the activity and purity of the rice husk, then neutralized to remove residual hydrochloric acid, and finally calcined at 550°C for 1h to obtain rice husk ash;
[0037] (2) 80 parts by weight of the pretreated regenerated micro powder and 20 parts by weight of rice husk ash are fully mixed in a mixer, and dry-mixed for 2 to 3 minutes to obtain powder A; at this time, the silicon-aluminum ratio in the powder A is 2:1;
[0038] (3) 20 parts by weight of sodium silicate solution, 6 parts by weight of sodium hydroxide and 10 parts by weight of deionized water were fully mixed, stirred until the sodium hydroxide was completely dissolved, and allowed to stand for 12 hours to obtain a solution B;
[0039] (4) Add powder A to a slurry mixer, slowly add solution B during the stirring process, and stir thoroughly for 3 to 5 minutes to obtain a geopolymer slurry;
[0040] (5) Pour the geopolymer slurry into a directional freezing device, set the freezing temperature to -20°C, the freezing direction from bottom to top, the freezing rate to 1°C / min, and freeze for 60 minutes. Freeze-dry the gradient pore structure geopolymer after freezing for 24 hours at a drying temperature of -15°C and a vacuum degree of 20Pa, and then steam cure for 7 days. The gradient pore structure geopolymer asphalt mixture warm mix is obtained by crushing and ball milling. The particle size of the gradient pore structure geopolymer after grinding is 35 μm, and the specific surface area is 200 m 2 / kg.
[0041] Depend on Figure 1 It can be seen that the geopolymer asphalt mixture warm mix prepared in Example 1 has abundant pores, and the pore sizes are arranged in a gradient, which is very important for increasing the water release cycle and ensuring the uniformity of the water release rate.
[0042] Example 2
[0043] The preparation method of the gradient pore structure geopolymer asphalt mixture warm mix agent of the present invention comprises the following steps:
[0044] (1) preparing 85 parts by weight of recycled micro powder, 15 parts by weight of rice husk ash, 20 parts by weight of sodium silicate solution, 5 parts by weight of sodium hydroxide and 10 parts by weight of deionized water;
[0045] (1.1) Pretreatment of the regenerated micropowder: first heat activation treatment at 750°C for 2 h, then ball milling for 10 min after cooling; the average particle size of the prepared regenerated micropowder is 45 μm, and the specific surface area is 400 m 2 / kg;
[0046] (1.2) Preparation of rice husk ash: First, the husk is soaked in hydrochloric acid to remove metal ion impurities such as iron ions to improve the activity and purity of the rice husk, then neutralized to remove residual hydrochloric acid, and finally calcined at 550°C for 1h;
[0047] (2) 85 parts by weight of the pretreated regenerated micro powder and 15 parts by weight of rice husk ash are fully mixed in a mixer, and dry-mixed for 2 to 3 minutes to obtain powder A; at this time, the silicon-aluminum ratio in powder A is 1.8:1;
[0048] (3) 20 parts by weight of sodium silicate solution, 6 parts by weight of sodium hydroxide and 10 parts by weight of deionized water were fully mixed, stirred until the sodium hydroxide was completely dissolved, and allowed to stand for 12 hours to obtain a solution B;
[0049] (4) Add powder A to a slurry mixer, slowly add solution B during the stirring process, and stir thoroughly for 3 to 5 minutes to obtain a geopolymer slurry;
[0050] (5) Pour the geopolymer slurry into a directional freezing device, set the freezing temperature to -20°C, the freezing direction from bottom to top, the freezing rate to 1°C / min, and freeze for 60 minutes. Freeze-dry the gradient pore structure geopolymer after freezing for 24 hours at a drying temperature of -15°C and a vacuum degree of 20Pa, and then steam cure for 7 days. The gradient pore structure geopolymer asphalt mixture warm mix is obtained by crushing and ball milling. The particle size of the gradient pore structure geopolymer after grinding is 35 μm, and the specific surface area is 200 m 2 / kg.
[0051] Example 3
[0052] The preparation method of the gradient pore structure geopolymer asphalt mixture warm mix agent of the present invention comprises the following steps:
[0053] (1) preparing 80 parts by weight of regenerated micropowder, 20 parts by weight of rice husk ash, 15 parts by weight of sodium silicate solution, 5 parts by weight of sodium hydroxide and 15 parts by weight of deionized water;
[0054] (1.1) Pretreatment of the regenerated micropowder: first heat activation treatment at 750°C for 2 h, then ball milling for 10 min after cooling; the average particle size of the prepared regenerated micropowder is 45 μm, and the specific surface area is 400 m 2 / kg;
[0055] (1.2) Preparation of rice husk ash: First, the husk is soaked in hydrochloric acid to remove metal ion impurities such as iron ions to improve the activity and purity of the rice husk, then neutralized to remove residual hydrochloric acid, and finally calcined at 550°C for 1h;
[0056] (2) 80 parts by weight of the pretreated regenerated micro powder and 20 parts by weight of rice husk ash are fully mixed in a mixer, and dry-mixed for 2 to 3 minutes to obtain powder A; at this time, the silicon-aluminum ratio in the powder A is 2:1;
[0057] (3) 15 parts by weight of sodium silicate solution, 5 parts by weight of sodium hydroxide and 15 parts by weight of deionized water were fully mixed, stirred until the sodium hydroxide was completely dissolved, and allowed to stand for 12 hours to obtain a solution B;
[0058] (4) Add powder A to a slurry mixer, slowly add solution B during the stirring process, and stir thoroughly for 3 to 5 minutes to obtain a geopolymer slurry;
[0059] (5) Pour the geopolymer slurry into a directional freezing device, set the freezing temperature to -20°C, the freezing direction from bottom to top, and the freezing rate to 1°C / min; freeze for 60 minutes, freeze-dry the gradient pore structure geopolymer after freezing for 24 hours, the drying temperature is -15°C, the vacuum degree is 20Pa, and then steam curing is performed for 7 days, and the gradient pore structure geopolymer asphalt mixture warm mix is obtained by crushing and ball milling. The particle size of the gradient pore structure geopolymer after grinding is 35μm, and the specific surface area is 200m 2 / kg.
[0060] Example 4
[0061] The preparation method of Example 4 is basically the same as that of Example 1, with the only difference being that during the pretreatment of the regenerated micropowder in step (1), the calcination temperature is 850°C.
[0062] Example 5
[0063] The preparation method of Example 5 is basically the same as that of Example 1, with the only difference being that during the pretreatment of the regenerated micropowder in step (1), the ball milling time is 15 min.
[0064] Example 6
[0065] The preparation method of Example 6 is basically the same as that of Example 1, with the only difference being that during the pretreatment of rice husk ash in step (1), the calcination temperature of rice husk ash is 750°C.
[0066] Example 7
[0067] The preparation method of Example 7 is basically the same as that of Example 1, with the only difference being that the directional freezing temperature in step (5) is -30°C.
[0068] The gradient pore structure geopolymer asphalt mixture warm mix agent prepared in Examples 1 to 7 was used to prepare warm mix asphalt mixture, and its performance was tested. The gradation type of the selected warm mix asphalt mixture was AC-13, 1# and 2# were limestone, 3# and 4# were basalt, the mineral powder was limestone, and the asphalt was SBS modified asphalt.
[0069] The gradient pore structured geopolymer asphalt warm mix agent prepared in Examples 1 to 7 was added to the warm mix asphalt mixture in place of mineral powder at 5% of the mass of asphalt.
[0070] Comparative Example 1 is a conventional hot-mix AC-13 asphalt mixture without adding a gradient pore structure geopolymer asphalt mixture warm mix agent.
[0071] Preparation of warm mix asphalt mixture of the present invention:
[0072] (1) Use an oven to preheat the aggregate and mineral powder to 130-150°C, and heat the asphalt to 145-165°C;
[0073] (2) When the temperature of the mixing pot reaches 130-150°C, pour the heated aggregate into the mixing pot and dry mix for 90 seconds;
[0074] (3) Add asphalt and gradient pore structure geopolymer asphalt mixture warm mix into a stirring pot and stir for 90 seconds;
[0075] (4) Add the heated mineral powder into the stirring pot and stir for 90 seconds;
[0076] (5) The molding temperature was controlled at 130° C. According to the Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering (JTGE20-2011), asphalt mixture specimens based on the warm mix agents of Examples 1 to 7 were prepared. The test results are shown in Table 1.
[0077] Comparative Example 1
[0078] Hot mix asphalt preparation:
[0079] (1) Use an oven to preheat the aggregate and mineral powder to 165-175°C, and heat the asphalt to 165-175°C;
[0080] (2) When the temperature of the mixing pot reaches 165-175°C, pour the heated aggregate into the mixing pot and dry mix for 90 seconds;
[0081] (3) Add asphalt into a mixing pot and stir for 90 seconds;
[0082] (4) Add the heated mineral powder into the stirring pot and stir for 90 seconds;
[0083] (5) The molding temperature was controlled at 155°C, and asphalt mixture specimens were prepared according to the Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering (JTGE20-2011). The test results of the asphalt mixture specimens of Comparative Example 1 are shown in Table 1.
[0084] Comparative Example 2
[0085] The commercially available Aspha-min (synthetic zeolite) warm mix agent was added to the warm mix asphalt mixture at 0.3% of the mass of the asphalt mixture.
[0086] Preparation of warm mix asphalt mixture based on Aspha-min (synthetic zeolite) warm mix agent:
[0087] (1) Use an oven to preheat the aggregate and mineral powder to 130-150°C, and heat the asphalt to 145-165°C;
[0088] (2) When the temperature of the mixing pot reaches 130-150°C, pour the heated aggregate into the mixing pot and dry mix for 90 seconds;
[0089] (3) Add asphalt and Aspha-min (synthetic zeolite) warm mix agent into a stirring pot and stir for 90 seconds;
[0090] (4) Add the heated mineral powder into the stirring pot and stir for 90 seconds;
[0091] (5) The molding temperature was controlled at 130 °C, and warm mix asphalt mixture specimens were prepared according to the Test Code for Asphalt and Asphalt Mixtures for Highway Engineering (JTGE20-2011). The test results are shown in Table 1.
[0092] Comparative Example 3
[0093] The preparation method of Comparative Example 3 is the same as that of Example 1, with the only difference being that rice husk ash is not added, and only recycled micropowder is used to prepare geopolymer asphalt mixture warm mix agent. Warm mix asphalt mixture specimens are prepared according to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011), and the test results are shown in Table 1.
[0094] Comparative Example 4
[0095] The preparation method of Comparative Example 4 is the same as that of Example 1, with the only difference being that the regenerated micropowder used to prepare the geopolymer asphalt mixture warm mix agent is not pretreated, and the warm mix asphalt mixture specimen is prepared according to the "Test Procedure for Asphalt and Asphalt Mixture for Highway Engineering" (JTG E20-2011), and the test results are shown in Table 1.
[0096] Comparative Example 5
[0097] The preparation method of Comparative Example 5 is the same as that of Example 1, with the only difference being that the geopolymer slurry is directly cured without directional freezing and freeze-drying. A warm-mix asphalt mixture specimen is prepared according to the Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering (JTG E20-2011). The test results are shown in Table 1.
[0098] Comparative Example 6
[0099] The preparation method of Comparative Example 6 is the same as that of Example 1, with the only difference being that the silicon-aluminum ratio in powder A is 3:1, which is not within the range of 2 to 1:1 required by this patent. A warm-mix asphalt mixture specimen is prepared according to the Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering (JTG E20-2011), and the test results are shown in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that the warm mix agent in Example 1 has the effect of significantly reducing the mixing and compaction temperature of the asphalt mixture, and the stability, dynamic stability, maximum flexural strain, water immersion residual stability, freeze-thaw splitting strength ratio and fatigue life of the prepared asphalt mixture are better than those of the hot mix asphalt mixture of the same gradation (Comparative Example 1).
[0103] Compared with Examples 2 to 7, the performance of the gradient pore structure geopolymer asphalt mixture warm mix agent prepared in Example 1 is the best, which is due to the fact that first, the mixing ratio of regenerated micropowder and rice husk ash directly affects the silicon-aluminum ratio of the geopolymer, which has an important influence on the mechanical properties, reaction activity and microstructure of the geopolymer; second, the difference in the alkali activator formula has a significant effect on the reaction rate of the geopolymer and the reaction degree of the silicon-aluminum raw materials; third, the calcination temperature and ball milling time during the pretreatment of the regenerated micropowder are important factors affecting the activity of the regenerated micropowder, and the calcination temperature and ball milling time in Example 1 have a better effect on stimulating its activity; fourth, the calcination temperature of rice husk ash directly affects its reaction activity and purity, and significantly affects the pore structure and mechanical properties of the geopolymer; fifth, the difference in freezing temperature affects the size of the temperature gradient and then affects the structure and distribution of the pores. Therefore, the gradient pore structure geopolymer asphalt mixture warm mix agent prepared according to Example 1 has a good warm mixing effect.
[0104] The gradient pore structure geopolymer asphalt mixture warm mix agent in the present invention is similar to the commercially available Aspha-min (synthetic zeolite) warm mix agent in principle. In order to study the water release process of the two warm mix agents, thermogravimetric analysis was performed on the two warm mix agents. The results are as follows: Figure 2 shown.
[0105] Depend on Figure 2 It can be seen that the gradient pore structure geopolymer asphalt mixture warm mix agent and Aspha-min (synthetic zeolite) warm mix agent of the present invention begin to lose water at 26°C and 22°C respectively. As the temperature continues to rise, the mass loss of the two warm mix agents shows an upward trend. Among them, the gradient pore structure geopolymer asphalt mixture warm mix agent has a relatively slow water release rate within 150°C, which can better ensure the continuous and stable release of water and the warm mixing effect is better. From the analysis of the total amount of water mass loss, it can be seen that the gradient pore structure geopolymer asphalt mixture warm mix agent of the present invention has a larger water load, which ensures the continuous output of water, and has more prominent advantages in reducing the viscosity of the asphalt mixture, improving the construction and workability, and improving the quality of the warm mix asphalt mixture.
Claims
1. A gradient pore structure geopolymer asphalt mixture warm mix agent, characterized in that: The invention is composed of the following components in parts by weight: 65-85 parts of regenerated micro powder, 15-35 parts of rice husk ash, 15-20 parts of sodium silicate solution, 5-10 parts of sodium hydroxide and 10-20 parts of deionized water.
2. The gradient pore structure geopolymer asphalt mixture warm mix agent according to claim 1, characterized in that: The regenerated micropowder is pretreated by the following method: the regenerated micropowder is first calcined at 750-950°C for 2-2.5 hours, and then naturally cooled and ball-milled by a planetary ball mill for 5-15 minutes. The average particle size of the prepared regenerated micropowder is 40-50 μm, and the specific surface area is 200-450 m 2 / kg.
3. The gradient pore structure geopolymer asphalt mixture warm mix agent according to claim 1, characterized in that: The rice husk ash is prepared by the following method: firstly, it is treated with hydrochloric acid, then it is neutralized and washed with water, and finally it is calcined at high temperature.
4. The gradient pore structure geopolymer asphalt mixture warm mix agent according to claim 3, characterized in that: The calcination temperature is 850-900°C, and the calcination time is 1-1.5h.
5. The method for preparing the gradient pore structure geopolymer asphalt mixture warm mix agent according to claim 1, characterized in that: The steps include: (1) Mixing the formulated amount of recycled micro powder and rice husk ash to obtain powder A, wherein the silicon-aluminum ratio in the powder A is 2 to 1:1; (2) mixing the sodium silicate solution, flaky sodium hydroxide and deionized water in the formula amount, stirring until the sodium hydroxide is completely dissolved, and then standing for aging to obtain solution B; (3) adding powder A into a slurry mixer, slowly adding solution B during the stirring process, and stirring thoroughly to obtain a geopolymer slurry; (4) placing the geopolymer slurry into a mold of a directional freezing device for rapid freezing treatment; (5) freeze-drying the gradient pore structure geopolymer obtained after the rapid freezing treatment, and then curing it. After curing, grinding it into powder to obtain a geopolymer asphalt mixture warm mix agent.
6. The preparation method according to claim 5, characterized in that: In step (2), the standing and aging time is 12 to 14 hours.
7. The preparation method according to claim 5, characterized in that: In step (4), the freezing temperature is -30 to -20°C, the freezing direction is from bottom to top, the freezing rate is 0.5 to 2°C / min, and the freezing time is 30 to 60 min.
8. The preparation method according to claim 5, characterized in that: In step (5), the freeze-drying temperature is -20 to -10°C, the vacuum degree is 10 to 30 Pa, and the drying time is 12 to 24 hours.
9. The preparation method according to claim 5, characterized in that: In step (5), steam curing is used for curing, and the curing period is 6 to 7 days.
10. The preparation method according to claim 5, characterized in that: In step (5), the particle size of the polymer with gradient pore structure after grinding is 25-45 μm, and the specific surface area is 150-250 m 2 / kg.
Citation Information
Cited By
Preparation method of elastic additive for recycled asphalt mortar
CN120398455A